Easy Microsoft Excel 2010 - Alexander, Michael, 1972- (Que, 2010)
This year, millions of beginner-to-intermediate-level users will be searching for the easiest possible way to master Excel 2010's new features - and, with Easy Microsoft Excel 2010, you'll find exactly what you're looking for. This full-color, utterly simple, step-by-step book has been carefully crafted to provide instant access to the 100+ tasks you'll find most useful and valuable. As with all books in the Easy series, it's designed to teach visually: you never have to work your way through lengthy text explanations. Its large typeface makes it even more accessible to all readers - especially senior readers whose needs are disregarded by most computer books. Written by an experienced Microsoft Excel trainer and author, Easy Microsoft Excel 2010 walks you through the easiest, fastest, most direct procedures for getting the results they're looking for. Coverage includes: getting started fast; managing, viewing, and editing workbooks; formatting data; using formulas, functions, charts, and graphics; analyzing data; printing; and even advanced techniques. Along the way, you will learn how to make the most of many of Excel 2010's most powerful innovations, such as Sparklines and the Excel Web App. 100+ hands-on, step-by-step tasks show novices and inexperienced upgraders the easiest, fastest, most direct way to accomplish common tasks Written by an experienced Microsoft Excel trainer and author Fully revamped for Excel 2010's most powerful new tools and features Large typeface improves readability and appeals to senior readers ignored by most computer books.